The role of formal education in the subjective well-being of young teenagers in rural and urban Peru - Cussianovich, A; Rojas, V (Palgrave Macmillan, 2014)
The main objective of this chapter is to examine the role that formal education plays in perceptions of their own well-being among a group of young Peruvians who live in a precarious economic situation and how this relates to their expectations. Young teenagers were interviewed around the time they were starting secondary school (2007) and, later on, around the time they were leaving, when some were moving into post-secondary education and others were entering full-time productive activities. This is a pivotal moment in the lives of young people: the end of their basic schooling and the time of their entry into the adult world.